Essays on Financing Decisions of Not-for-Profit Organisations - Jiang, Han (Université d'Ottawa / University of Ottawa, 2022)
Chapter 1 novelly examines the nature of the interaction between private donors and not-for-profit organisations (NPOs) when NPOs can invest endowment funds in a two-asset risky portfolio and donors can contribute to both the endowment fund and the annual campaign. I study a three-stage non-cooperative game with two types of economic agents: a cohort of heterogeneous donors and one representative NPO. In equilibrium, donors always contribute to the endowment fund; however, they may not contribute to the annual campaign. The proportion of the NPO's endowment fund invested in the risky asset is a discontinuous function of the endowment; donors contribute less to an aggressive NPO and more to a cautious one. When the NPO can solicit donors to contribute only once, this increases the expected level of the contribution in equilibrium, but this may not generate higher expected utility for donors. Chapter 2 presents a dynamic model of charitable giving. At each period, donors contribute to an NPO's endowment; the NPO provides a charitable good and invests in the  financial market. Investments are made in a risky asset and a risk-free asset. I introduce two types of shocks to account for uncertainty: donors' income shock and  financial market fluctuations. I show that the optimal share of disposable endowment invested in risky asset is constant. Donors' strategy, whether to contribute or free-ride on the NPO's investments, depends on donors' shadow prices. Donors contribute when NPO's endowment is relatively low. Large contribution levels encourage the NPO to participate in the capital market at the expense of providing charitable good. I show that the NPO prefers an environment with a lower rate of return on risk-free assets. NPO's risk exposure to the  financial market affects both NPO's and donors' decisions. However, risk exposures on donors' side do not impact parties' decisions. Regulation analysis suggests that portfolio ceiling and provision floor are achievable. Chapter 3 links two data sources: the National Center for Charitable Statistics (NCCS) data over the period of 1987-2014 and the U.S. presidential elections data. I develop a dynamic model to examine how the national-level political incumbent shapes the NPOs' risky investment portfolio selection, adjusting for a set of NPOs' intrinsic characteristics and real interest rate. I  find that right-leaning Republicans act as a rein on NPOs' risky investments, i.e., a Republican administration is associated with a reduction in NPOs' holdings of corporation stocks and a 16.28% reduction in equity share relative to a Democratic administration. It is attributed to the impact of the Republican administration by more facilitating NPOs' accessibility to borrowing than having a Democratic president. I argue that NPOs behave as backward-looking investors or are reluctant to change their portfolio due to the significant portfolio adjustment cost, using past performance as an indicator to make their current risky investment decisions. Heckman two-step estimation indicates that NPOs' investment is an endogenous sample selection instead of a random choice. I show that NPOs have a less extensive equity share with more severe agency costs; foundation size plays a different role when NPOs decide whether to invest in risky assets compared with investing NPOs. Moreover, for investing NPOs, the equity share is expected to decrease by 12.0% if there is a 1% increase in the real interest rate; NPOs are more inclined to invest in risky assets when the real interest rate increases, in the sense of riding with the rational bubble.
Keywords: NPO; Financing Decisions; Game Theory; Political Incumbent